WATER QUALITY IN THE NORTH MADURA : IS IT SUITABLE FOR VANNAMEI SHRIMP FARMING OR NOT? - Santanumurti, Muhammad Browijoyo; Samara, Syifania Hanifah; Nindarwi, Daruti Dinda (AQUASAINS, 2019)
Indonesia is one of the countries with the highest potential and production of vannamei shrimp (Litopenaues vannamei) in the world. Therefore, the government continues to improve theactivity of vannamei shrimp farming continuously. This study aimed to determine whether the water quality of the waters in Larangan Glintong Village, Bangkalan-Madura, East Java was suitable for vannamei shrimp farming activities. Water quality was one of the keys for successful vannamei shrimp farming since it could affect the metabolism, reproduction, osmoregulation and stress of the organism. The parameter water quality used in this study was salinity, temperature, and pH. This research was a water quality survey that was carried out for three months (March-May). The result showed that the average water salinity was 30.5 ppt. The average DO and brightness showed 7.02 mg/l and 30.69 cm. The average temperature at there was 29.41oC while the pH valued showed 8.13. The It could be concluded from water quality aspect that pond in Larangan Glintong Village, Bangkalan-Madura could be used for vannamei aquaculture development.